Una “natura” in ansia: l’identità umana alla prova della tecnica e della globalizzazione. Una glossa sul lessico dell’alterità - Mazzarella, Eugenio (Bollettino Filosofico, 2019)
The contribution intends to reflect on the marginalization of the human, which in different forms is implemented by the progress of an increasingly technologized and globalized society. In dialogue with authors such as Bauman, Anders and Heidegger, the paper focuses on the main situations in which, in contemporary society, technique and globalization make the human being peripheral to himself. This marginalization strongly challenges the meaning and value of human dignity through dynamics that are often all the more insidious as they are not immediately noticeable. Faced with this scenario, the refuge of philosophy in an anthropology that merely describes a dimension beyond the human seems unable to recover the primitive link between the human being and his world, that is between the human being and his situation of being. Keywords: Globalization, Technique, Human, Otherness, Nature